PELAKSANAAN PENILAIAN PRESTASI KERJA DAN HUBUNGANNYA DENGAN MOTIVASI KERJA KARYAWAN - Syahyuni, Dedy (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
ABSTRACT Performance appraisal is one of the thing that human resource management department conducted in a company. In every year or on in every six months company conducted performance appraisal. Performance appraisal is the method that human resource use to see the employee performance in one period. The things that performance appraisal see like how work done, how the employee work with others, how the discipline of the employee, and others things. With the performance appraisal companies can know the level of accomplishment of employee works as a part of a team or as an individual. Employee achievements can be assessed and monitored from this process. With performance appraisal, achievement and shortcomings of a work from employee can be monitored clearly. From this method, human resource can track all aspect from employee like motivation, effectiveness, efficiency, the work load, job satisfaction from time to time. With this method also, company can make a plan for employee like career path, employee development, salary and other things.With this method also, company can see the progress that employee achieve from year to year. But sometimees the performance appraisal is done in a way that improperly or at least inadequate procedures. biases of standard and subjectivity are usually the things that become problems in performance appraisal. For example, Sometimes the standar value from performance appraisal is not match with the work or sometime standar operation and procedur that not clear. The cause or problems that sometime we see in company that use the wrong way to conduct performance appraisal can sometimes can be a fatal problem. Employee can be demotivation, un satisfied with the work or with the company, not effective and or not efficient with the work or maybe be a rebel to his team or his team work.Keyword: Employment, Human Resource, Performance appraisal, Motivation, Work